Perceived fairness in Islamic home financing: Comparison between Al-Bay’bithaman Ajil and Musharakah Mutanaqisah partnership contracts - Noordeen, Mohamed Imtiyaz; Kassim, Salina; Haron, Nor Zalina (Malaysia Institute of Planners, 2017)
While many see housing sector as a commodity, there are still many people in Malaysia who fail to own homes and many are forced to rent or stay away from urban areas. This paper aims to provide information and disclosure of available loan opportunities for house purchases in Malaysia. Apart from the importance among buyers, it is also seen as important from the perspective of property valuers and professionals involved in housing industry. Thisstudy compares the perceive fairness between three types of home financing that are available in Malaysia, namely conventional home loan, al-bay’ bithaman ajil, and musharakah mutanaqisahpartnership (MMP) contracts among the customers in Malaysia. The study conducts a survey among 100 respondents to examine the relationship betweencustomer intentions to use Islamic home financing based of MMP. The study concludes that the MMP has several advantages and cheaper over the BBA for the customer. Apart from being unanimity Shari’ah-compliant, it can be made to keep away from interest completely by means of practicing rental or house price index at the same time as reducing the cost of homes and the duration of financing. This paper concludes by suggesting recommendations for the appropriate actions to address the issues and challenges facing the MMP home finance products and deregulate BBA in Malaysia.